How independent? an analysis of GE13 coverage by Malaysia’s online news portal coverage - J, Lumsden Linda (Universiti Kebangsaan Malaysian, 2013)
The May 5, 2013, general election in Malaysia may have marked the move of the nation’s alternative news media—online, unlicensed news portals that challenge the hegemony of the party that has ruled the nation since 1957—into the mainstream. Malaysiakini, The Malaysian Insider, and Free Malaysia Today editors pride themselves on their independence and journalistic role as government watchdogs, a role they claim has been abdicated by newspapers and broadcast outlets. This article critiques the self-professed editorial independence of these three online news portals through analysis of their GE13 campaign coverage. This research will expand knowledge about Malaysia’s evolving news environment and will add to research on media coverage of previous Malaysian elections. The study employs two research methods: content analysis and personal interviews with news portal editors and media scholars. Following an overview of Malaysia’s historically hegemonic mainstream news media, the article traces how the Internet facilitated the introduction of Malaysia’s counter-hegemonic online news portals. Its basic research question is: Did Malaysia’s leading independent news portals provide unbiased news coverage of GE13? The hypothesis was that the sites would be negatively biased against the ruling Barisan Nasional coalition and positively biased toward opposition coalition candidates, However, the study found 8.2 percent more positive BN stories than negative BN stories in overall coverage. A greater disparity appeared in opposition coverage, where positive stories as predicted outnumbered negative stories by 56.1 percent. News portals criticized both parties, leading to the conclusion that they add to the political discourse that is requisite for successful participatory democracy.